Pengembangan Sumber Belajar Matematika Berbentuk Slideshow Interaktif - Varetha Lisarani (Journal of Instructional Mathematics, 2021)
The purpose of this research and development is to describe the process and results of the development of mathematics learning resources in the form of interactive slideshows of Linear Equations of Two Variables topic for junior high school students of 8th grade. This development was carried out because of the need for interactive learning resources that are easy to develop and operate by both teachers and students during the implementation of Distance Learning (Pembelajaran Jarak Jauh) in this New Normal era. The development model used in this research is a modification of the Plomp model, which includes the phases of initial investigation, design, realization and test, evaluation, and revision. Even though the development process is simple, the results of the validation of this learning resource indicate that the product is valid with a percentage of 85.8% from the expert validation sheet, and is effective because 100% of students who are the subject using this learning resource get a score of more than 75 and 92% of students respond positively.